2017
DOI: 10.1016/j.bmc.2016.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Highly predictive and interpretable models for PAMPA permeability

Abstract: Cell membrane permeability is an important determinant for oral absorption and bioavailability of a drug molecule. An in-silico model predicting drug permeability is described, which is built based on a large permeability dataset of 7488 compound entries or 5,435 structurally unique molecules measured by the same lab using parallel artificial membrane permeability assay (PAMPA). On the basis of customized molecular descriptors, the support vector regression (SVR) model trained with 4,071 compounds with quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 30 publications
1
67
0
Order By: Relevance
“…To determine the capacity to reach the CNS, the permeability must be evaluated. To analyze the passive permeability characteristics of API, we measured BBB permeability by a PAMPA model, well adapted to High Throughput Screening (HTS) [41]. Theophylline (Pe = 5.0 ± 0.0 nm/s), and corticosterone (Pe = 202.0 ± 3.0 nm/s) were used as low and high permeability standards, respectively.…”
Section: Characterization Of the Active Pharmaceutical Ingredient (Api)mentioning
confidence: 99%
“…To determine the capacity to reach the CNS, the permeability must be evaluated. To analyze the passive permeability characteristics of API, we measured BBB permeability by a PAMPA model, well adapted to High Throughput Screening (HTS) [41]. Theophylline (Pe = 5.0 ± 0.0 nm/s), and corticosterone (Pe = 202.0 ± 3.0 nm/s) were used as low and high permeability standards, respectively.…”
Section: Characterization Of the Active Pharmaceutical Ingredient (Api)mentioning
confidence: 99%
“…Parallel artificial membrane permeability assays (PAMPA) were used to model passive, transcellular permeability across the gastrointestinal tract (GIT) (41). All compounds tested were characterized as highly permeable (>100 x 10 -6 cm/s) (Supplemental Table 1).…”
Section: In Vitro Drug Metabolism and Pharmacokinetic Properties Of Mmentioning
confidence: 99%
“…This permeation is energy independent, 38 and it provides permeability values that are useful for oral absorption predictions, because the majority of drugs are absorbed by passive diffusion through the membrane. [39][40][41] The improvement in solubility and dissolution (in vitro release) of Cur in RA-Cur contributed to the enhanced permeation. These results suggested that the oral bioavailability of Cur would be improved in in vivo experiments using RA-Cur.…”
Section: Discussionmentioning
confidence: 99%